Co-creating welcome - design interventions on entrances for thriving commons - Björnberg, Maria (My University, 2021)
This master thesis explores how an embedded co-designer can contribute to create welcoming processes and places through shaping design interventions on entrances to commons. The methods both originate from an ethnographic design approach as well as an action-research based approach. The framework proceeds both from theory and examples within the notions of commons, exploring its resources, community and commoning, yet also with approaches and tools from the notion of place making. The main case of exploration is the peri-urban land-based commons Eco Agroforestry Center, located in north-east of Gothenburg, Sweden, with a deepened focus on one of its entrances to the outdoor site. Based on that entrance, the specific needs of the commons, as well as the framework, key principles are developed both to create a welcoming place, but also a welcoming process. During the co-creational process four design factors and tools are developed - movement (threshold theory), way (willow weaving), form (portal & arches) and function (diverse seatings) - that are applied to a number of design interventions. Through the methods of discussions, mapping, site explorations, photosketching, photo-collages, prototyping, testing, expert-input, models, building and communication the design interventions are being shaped. The culmination of the realised design interventions is a cocreating exhibition including the intervention artefacts at the site. However, future interventions are proposed, and two scenarios are collaged to show potential outcomes: the thriving commons and the forgotten place.
Keywords: Commons, place making, design, interventions, co-creation